Terapi Musik Angklung Dalam Kelompok Untuk Peningkatan Keterampilan Sosial Pada Orang dengan Skizofrenia - Puri Yogyantoro (Jurnal Psikologi, 2022)
This research aims to determine the improvement of social skills in people with schizophrenia by having given Angklung music therapy in the same time. The type of study used Single Case Ekperimental Design, where the design of the experimentally A-B-A form by evaluating the effect of a treatment by way of comparing the condition of the subject over time where the subject was observed in his skills in Condition of treatment and with interchangeably treatment. Skills in people with schizophrenia observable are listening skills, skills making, demand skills, revealing feelings of fun and expressing unpleasant feelings. The data analysis techniques used in this study use visual inspection using observations performed by 3 raters. The early termination behavior of the increase in each phase, the average of the A1 phase listening skills from (3) to (3.9) in phase B then (5.3) in phase A2. The results of observation observations make the A1 phase request from (2.6) to (3.6) in phase B and increase to (5.3) in phase A2. The results of behavioral observations reveal a pleasant expression could not be observed as a result of the research process, while the average skills expressed unpleasant feelings from (1.9) in the A1 phase increased to (2) in phase B and became (2.1) in phase A2. The baseline chart results obtained from observation can be concluded that there is a social skill increase in the subject that initially was at a very low level in phase A1 (8) to phase B (10) and to phase A2 (13) as well as the follow up phase (13) at the level of the Low. It shows people with schizophrenia experiencing increased social skills after being given group music therapy so that music therapy can be an alternative to improving social skills.